Analisis Peran BUMDes sebagai Ruang Kewarganegaraan Aktif melalui Studi Kasus Program Pengelolaan Sampah di Desa Marindal I - Marly Meani Silalahi; Nazlah Aulia; Esra Natasya Br Sitepu; Johan Pardamean Simanjuntak; Halking Halking (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
This study aims to analyze the role of Village-Owned Enterprises (BUMDes) in creating spaces for active citizenship through the implementation of a Waste Management Program in Marindal I Village. The background of this research is based on the growing waste management challenges in peri-urban areas, which require active community involvement and the strategic role of village institutions. This study employs a qualitative method with a descriptive approach. Data were collected through field observations, in-depth interviews, and documentation involving BUMDes managers, village officials, and community members as key program stakeholders. The findings indicate that BUMDes plays a significant role as a facilitator and mobilizer of community participation by encouraging residents to engage in waste collection, sorting, and processing activities with economic value. The implementation of the program not only enhances environmental awareness and responsibility but also strengthens social cooperation, collective accountability, and the practice of active citizenship at the village level. Furthermore, BUMDes-based waste management contributes to increased village revenue through the utilization and sale of recycled materials.